Optimal Overcurrent Relay Coordination Using Optimized Objective Function. (3rd April 2014) - Mousavi Motlagh, Seyed Hadi; Mazlumi, Kazem
Abstract : A novel strategy for directional overcurrent relays (DOCRs) coordination is proposed. In the proposed method, the objective function is improved during the optimization process and objective function coefficients are changed in optimization problem. The proposed objective function is more flexible than the old objective functions because various coefficients of objective function are set by optimization algorithm. The optimization problem is solved using hybrid genetic algorithm and particle swarm optimization algorithm (HGAPSOA). This method is applied to 6-bus and 30-bus sample networks.